2010
DOI: 10.1016/j.cell.2010.10.014
|View full text |Cite
|
Sign up to set email alerts
|

A Family of Protein-Deglutamylating Enzymes Associated with Neurodegeneration

Abstract: Polyglutamylation is a posttranslational modification that generates glutamate side chains on tubulins and other proteins. Although this modification has been shown to be reversible, little is known about the enzymes catalyzing deglutamylation. Here we describe the enzymatic mechanism of protein deglutamylation by members of the cytosolic carboxypeptidase (CCP) family. Three enzymes (CCP1, CCP4, and CCP6) catalyze the shortening of polyglutamate chains and a fourth (CCP5) specifically removes the branching poi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

28
523
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 323 publications
(554 citation statements)
references
References 45 publications
28
523
2
1
Order By: Relevance
“…Recombinant Nna1, CCP4, and CCP6 Metabolize the Polyglutamate Side Chain of Tubulin-Previous enzymatic studies of Nna1 family members were performed using tubulin as substrate and lysates of cells transfected with CCP4 and CCP6 as a source of enzyme with detection using an antibody to the polyglutamate chain of tubulin (10). As it is not practical to use this approach to determine details of enzyme kinetics or substrate preferences, we generated and purified N-terminally histidinetagged versions of Nna1 (7) and CCP4 and CCP6 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recombinant Nna1, CCP4, and CCP6 Metabolize the Polyglutamate Side Chain of Tubulin-Previous enzymatic studies of Nna1 family members were performed using tubulin as substrate and lysates of cells transfected with CCP4 and CCP6 as a source of enzyme with detection using an antibody to the polyglutamate chain of tubulin (10). As it is not practical to use this approach to determine details of enzyme kinetics or substrate preferences, we generated and purified N-terminally histidinetagged versions of Nna1 (7) and CCP4 and CCP6 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We suggested that this might be a consequence of overlapping expression or redundancy with other Nna1 subfamily members, such as CCP4 and CCP6 (3), that are reported to catalyze the identical glutamase reaction in vitro (10). The primary objectives of this study were to determine whether the three CCPs have identical enzymatic and functional properties and whether these properties are consistent with the enzymes contributing to the selective neurodegeneration in pcd mice.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This protein has a role in protein turnover by cleaving proteasome-generated peptides into amino acids (Berezniuk et al, 2010), enzymatically removing geneencoded glutamic acids or tyrosine from the C-terminus of proteins (Rogowski et al, 2010, Kalinina et al, 2007 and also has a role in neuronal bioenergetics at least in mouse brains (Chakrabarti et al, 2010). Similar to other cytosolic carboxypeptidases, the mouse Nna1 protein is broadly expressed in the brain, pituitary, eye, testis and other tissues (Kalinina et al, 2007).…”
Section: Discussionmentioning
confidence: 99%